Risk Factors for Sleep Disorders in Patients with Chronic Pain: A Meta-Analysis - Yoerizta Ratu, An Nissa’; Arina Widya Murni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Chronic pain and sleep disorders frequently co-occur, exacerbating each other in a vicious cycle. This meta-analysis aimed to identify and quantify risk factors associated with sleep disorders in individuals experiencing chronic pain. Methods: A systematic search of PubMed, Embase, Web of Science, and Cochrane Library databases was conducted from January 2018 to June 2024. Studies assessing sleep disorders (insomnia, obstructive sleep apnea, restless legs syndrome) in adults with chronic pain (non-cancer pain lasting >3 months) were included. Data on demographics, pain characteristics, sleep measures, and potential risk factors were extracted. Meta-analyses were performed using random-effects models to estimate pooled odds ratios (ORs) and 95% confidence intervals (CIs). Results: Twenty-seven studies (n = 12,453 participants) met the inclusion criteria. Chronic pain significantly increased the odds of having any sleep disorder (OR 2.83, 95% CI 2.19-3.65). Specific risk factors identified included: Female gender: OR 1.41 (95% CI 1.18-1.67); Higher pain intensity: OR 1.15 per 1-unit increase on a 0-10 scale (95% CI 1.08-1.23); Longer pain duration: OR 1.04 per year (95% CI 1.01-1.07); Presence of depression or anxiety: OR 2.32 (95% CI 1.85-2.91); Use of opioid medications: OR 1.58 (95% CI 1.23-2.04). Conclusion: Chronic pain is a substantial risk factor for sleep disorders. Gender, pain intensity, duration, comorbid mental health conditions, and opioid use emerged as modifiable risk factors. Targeted interventions addressing these factors may improve sleep outcomes in individuals with chronic pain.